Failure is not an option: learner persistence amongst Access to Higher Education learners on a DipHE/BSc nursing programme - Hinsliff-Smith, Kathryn (2013)
Since the late 1990s, the UK Government has a policy to support Widening Participation (WP) measures in UK universities. These measures aimed to increase the demographic and socio-economic profile of the undergraduate student population across all UK universities. The target for these measures includes a focus on mature applicants, women entrants, and ethnic minority representation. Latest data (2010/2011) from the Higher Education Statistics Agency (HESA) indicates whilst by far the largest proportion of full-time entrants to undergraduate places are the ‘traditional’ 19 year entrant with A level qualifications (288,590). By comparison a further 77,155 entrants are mature, those aged over 21, who have gained a variety of accepted entry qualifications. One such recognised qualification is that of an Access to Higher Education Diploma. The Access programme is usually undertaken by mature students, with no previous qualifications, who after successful completion of a one-year full-time course are then able to apply for an undergraduate course. It is estimated that one in four mature entrants will enter a university course with an Access qualification (HEFCE, 2006).